Design and Operation of Very Slow-Speed Generators for a Bristol Cylinder Sea Wave Generating Device - Sze, S.N; Dorrell, D.G; Cossar, C. (IEEE, 2012)
This paper describes the operation of a direct-drive brushless generator for a Bristol cylinder ocean wave device. This is a very low speed device so the pole number and diameter is very large. While the machine may be large the pole pitch and axial length is low. The application is described and simulated using analytical and finite element analysis techniques. A 248 pole design with surface rotor magnets is developed with both surface and slotted windings. An analysis of the control is put forward.